Implementation of Lean Manufacturing as the Main Foundation of Effective Operational Management - Imam Wibowo (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
Lean Manufacturing is known as an approach that focuses on eliminating waste and increasing the efficiency of the production process. This research aims to explore and analyze the implementation of Lean Manufacturing as the main basis for achieving effective operational management. This research uses a qualitative approach with descriptive methods. The results of this research indicate that the implementation of Lean Manufacturing as the main foundation for effective operational management has a significant positive impact on company performance. Through planned and sustainable steps, the company succeeded in reducing waste in the production process, increasing operational efficiency, and creating a more structured and productive work environment. Continuous monitoring and evaluation proves that the continuous improvements adopted, such as the implementation of 5S, Kaizen, and the Just In Time concept, consistently result in increased production cycle time efficiency and improved product quality. In addition, active employee participation in continuous improvement initiatives has been proven to make a positive contribution to a company culture that is responsive to change. By integrating the PDCA cycle, the company succeeded in maintaining the continuity of the Main Foundation of Effective Operational Management based on Lean Manufacturing, creating a solid foundation for operational growth and continuity in a dynamic business environment.